"Can You Help Me?" An Experience Report of Teamwork in a Game Coding Camp for Autistic High School Students - Moster, Makayla; Kokinda, Ella; Re, Matthew; Dominic, James; Lehmann, Jason; Begel, Andrew; Rodeghero, Paige (ICSE 2022, 2022)
Teamwork skills are increasingly important for students to have as they enter the workforce, especially in software development positions. However, autistic students do not get to practice teamwork since much of their education is focused on learning social skills. Social skills are important for teamwork, since autistic students have trouble deciphering social norms as part of a team, and even more-so in a remote learning environment. The hybrid mode of education comes with challenges, including communication and collaboration issues and teaming difficulties. This method of teaching and learning can be difficult for students with autism. In this experience report paper, we discuss our experience planning and running a hybrid camp to teach teamwork and programming to autistic high school students. We detail our lessons learned and provide recommendations for educators and researchers working with autistic students in a hybrid setting.